2003
DOI: 10.1097/00004032-200302000-00004
|View full text |Cite
|
Sign up to set email alerts
|

UPTAKE OF 137Cs AND 90Sr IN RICE PLANTS

Abstract: In order to study the transfer of water-borne 137Cs and 90Sr into rice plants, pot experiments were done by growing rice plants on soils taken from rice beds near two nuclear power plants: Qinshan Nuclear Power Plant and Daya Bay Nuclear Power Plant in China. The vertical migration of 137Cs and 90Sr in the soil samples was studied, and results show that almost all the contaminants were retained in the top 1 cm of soil with at most a few percent down to 3 cm of soil. The areal transfer factors of 137Cs and 90Sr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
21
1

Year Published

2003
2003
2012
2012

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 20 publications
(26 citation statements)
references
References 11 publications
4
21
1
Order By: Relevance
“…A solution to the problem is to use the areal transfer factor (TF a , m 2 kg ÿ1 ), which is based on the unit-area deposition (Bq m ÿ2 ) at different growth stages. The term, areal transfer factor, is cited from Leung and Shang (2003).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A solution to the problem is to use the areal transfer factor (TF a , m 2 kg ÿ1 ), which is based on the unit-area deposition (Bq m ÿ2 ) at different growth stages. The term, areal transfer factor, is cited from Leung and Shang (2003).…”
Section: Introductionmentioning
confidence: 99%
“…Almost nothing is reported about the TF a values for rice except for the works of Choi et al (1995); Choi et al (2002a) and Leung and Shang (2003).…”
Section: Introductionmentioning
confidence: 99%
“…After the Chernobyl accident, there was further interest . Owing to its chemical and physiological similarity with potassium, 137 Cs can easily enter into the food chain and become an important contributor to internal radiation dose of animal bodies Leung and Shang, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…A similar type of transfer factor determination work has been carried out by Beresford and Howard (1991) and El-Reefy et al (2006) where they have used unwashed vegetables/ grass which were fed to animals and thus can be compared with the present study. Leung and Shang (2003) reported that stem and leaves accumulate most of the 137 Cs compared to rice seed which carries the least concentration of 137 Cs. It was observed that transfer factor for 40 K was found to be >1 and that of 137 Cs was <1.…”
Section: Transfer Of 137 Cs and 40 K Through Soil-vegetation Pathwaymentioning
confidence: 99%